What's a middle school teacher to do? Five evidence-based practices to support English learners and students with learning disabilities - Hovey, Katrina A.; Miller, Rhonda D.; Kiru, Elisheba W.; Gerzel-Short, Lydia; Wei, Yan; Kelly, Jerae (Preventing School Failure: Alternative Education for Children and Youth, 2019)
General education teachers are challenged with meeting the unique instructional needs of every learner in their classrooms, which increasingly include English learners (ELs) and students with learning disabilities (LD). This article uses vignettes to demonstrate how a middle school content teacher uses five strategies: building prior knowledge, building vocabulary, explicit instruction, visual representation, and opportunities to respond to support his students. Each strategy is evidence based for ELs and for students who have an identified LD. Research supports that ELs and students with LD benefit from specific instructional strategies that enhance the accessibility of course content and potentially improve learning outcomes. © 2019, © 2019 Taylor & Francis Group, LLC.
Keywords: English learners; dept.rdg; dept.sed; evidence-based strategies; instructional practices; learning disabilities; peer-reviewed

Engaging culturally and linguistically diverse families of children with disabilities - Gerzel-Short, Lydia; Kiru, Elisheba W.; Hsiao, Yun-Ju; Hovey, Katrina A.; Wei, Yan; Miller, Rhonda D. (Intervention in School and Clinic, 2019)
Classrooms are increasingly more diverse, and student success can be enhanced through family engagement, especially for culturally and linguistically diverse (CLD) students with disabilities. Too often teachers are stymied by how to engage CLD families of children with disabilities. Common practices of parent involvement are ineffective and fail to appreciate families as members of the educational team. Family engagement seeks to establish and maintain authentic family-school partnerships based on mutual respect and shared agency for student academic and social success. This column provides specific family engagement strategies that teachers and schools can implement in an effort to provide reciprocal collaboration.
Keywords: cultural and linguistic diversity; dept.rdg; dept.sed; disabilities; diverse families; family engagement; family-school collaboration; multicultural; peer-reviewed